예인수조와 캐비테이션 터널에서 프로펠러 단독특성의 실험적 상호관계 해석 - 김기섭(K.-S. Kim); 김경열(K.-Y. Kim); 안종우(J.-W. Ahn) (大韓造船學會 論文集, 2000)
This paper presents the influence of Reynolds number on propeller open-water performance at the towing tank and the cavitation tunnel for series propellers(No. of blade=4, $0.3{≤}A_E/A_O{≤}0.75,\;0.5{≤}P/D{≤}1.1$). It is shown that the Reynolds number recommanded by 15th and 17th ITTC is not large enough to obtain reliable P.O.W. test results and then the suitable test conditions for the both facilities is suggested. The correlation of the propeller open-water characteristics at the cavitation tunnel and the towing tank is described and a correlation factor $κ$ is deduced from those test results. The viscous effect of the flow around the propeller shaft on the propeller characteristics is investigated from the velocity measurement by Laser Doppler Velocitimetry(L.D.V.). The measured velocity distribution shows that viscous flow effect is not negligible. 예인수조와 캐비테이션 터널에서 레이놀즈 수가 프로펠러 단독 특성시험에 미치는 영향을 씨리즈 모형 프로펠러(날개수=4, $0.3{≤}A_E/A_O{≤}0.75,\;0.5{≤}P/D{≤}1.1$)에 대하여 실험적인 방법으로 조사하였다. 예인수조에서 프로펠러 단독 특성시험을 위한 시험조건으로 제15차와 17차 ITTC에서 추천한 레이놀즈 수($R_n{≥}3.0{×}10^5$)는 시험조건으로써 불충분함을 보였으며 적합한 시험조건 선정방법을 제안하였다. 예인수조와 캐비테이션 터널에서 프로펠러 단독특성들의 상호관계를 나타내는 상관계수($κ$)를 도출하였다. 프로펠러 축 주위에서 형성된 경계층 유동이 프로펠러 특성에 미치는 영향을 레이저 유속계를 이용한 계측에 의해 조사하였으며, 그 영향이 작지 않다는 것을 보였다.